The Effect of Integrated Antenatal Care on Planning for Birth in Pregnant Women - Saidudah Saidudah; Novita Novita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The purpose of this study was to determine the effect of integrated antenatal care on delivery planning for pregnant women. Methods: This type of research is a quasi-experimental conducted in the Binuang Health Center area in April – May 2022, the number of samples is 46 respondents, and the type of statistical test used is the Wilcoxon test Results: Show a p-value of 0.001 < 0.05, meaning that there is an effect of Integrated Antenatal Care on Delivery Planning Conclusion: Conclusion of this study is that the provision of antenatal care has an effect on delivery planning.